Effectiveness of individually tailored exercise on functional capacity and mobility in nursing home residents. (2nd March 2021) - Bertoncello, Chiara; Sperotto, Milena; Bellio, Stefania; Pistellato, Ilaria; Fonzo, Marco; Bigolaro, Chiara; Ramon, Roberto; Imoscopi, Alessandra; Baldo, Vincenzo
Abstract : Deterioration of physical and functional capacities is often seen in nursing homes. The present study aimed at assessing the effectiveness of an individually tailored physical exercise intervention on mobility and functional decline in nursing home residents in a 1-year follow-up period. Information on gender, age, education, profession and cognitive status was collected at baseline and at 6 and 12 months of the intervention. The decline in functional capacity and mobility was assessed using the Barthel index. Some 221 participants were included. Results from the multivariate logistic regression showed how residents who never participated in physical activities had a five-fold higher risk of mobility decline compared with residents who did engage for the whole follow-up time. A lower effect was seen in residents who participated for only 6 months. Although dementia appeared to be a significant predictor of decline, a substantial stabilisation in mobility capacity was noted in patients with both mild and severe dementia performing exercise. The findings suggest that preventing or slowing physical decline in nursing home residents is an achievable goal, and even those with a higher degree of cognitive decline may benefit from a tailored physical activity plan.